2020
DOI: 10.1093/dnares/dsaa016
|View full text |Cite|
|
Sign up to set email alerts
|

Genome sequencing of four culinary herbs reveals terpenoid genes underlying chemodiversity in the Nepetoideae

Abstract: Species within the mint family, Lamiaceae, are widely used for their culinary, cultural, and medicinal properties due to production of a wide variety of specialized metabolites, especially terpenoids. To further our understanding of genome diversity in the Lamiaceae and to provide a resource for mining biochemical pathways, we generated high-quality genome assemblies of four economically important culinary herbs, namely, sweet basil (Ocimum basilicum L.), sweet marjoram (Origanum majorana L.), oregano (Origanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 69 publications
5
28
1
Order By: Relevance
“…Then, the contigs were assembled by the DeNovoMagic assembler, and the final assembly consisted of 12,212 scaffolds with a total genome size of ∼2.13 Gbp, and less than 1.3% gaps ( Table 1 ). The genome size is in good agreement with that of Bornowski et al 15 who found a genome size of 2.07 Gbp. The N50 scaffold size was approximately 19 Mbp, and the N90 scaffold size was approximately 5.8 Mbp.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Then, the contigs were assembled by the DeNovoMagic assembler, and the final assembly consisted of 12,212 scaffolds with a total genome size of ∼2.13 Gbp, and less than 1.3% gaps ( Table 1 ). The genome size is in good agreement with that of Bornowski et al 15 who found a genome size of 2.07 Gbp. The N50 scaffold size was approximately 19 Mbp, and the N90 scaffold size was approximately 5.8 Mbp.…”
Section: Resultssupporting
confidence: 90%
“…Long-terminal repeats (LTRs) were the most commonly found types (48% of the genome), and of those, copia-like and gypsy were the most prevalent ( Table 2 ). These values are higher than those reported by Bornowski et al 15 who found 67% repetitive elements and 37% LTR elements.…”
Section: Resultscontrasting
confidence: 73%
See 3 more Smart Citations